Membrane ion conductances of mammalian skeletal muscle in the post-decompression state after high-pressure treatment. - Friedrich, Oliver; Kress, Kai; Ludwig, Horst; et al. (Journal of Membrane Biology, 2002)
Exposure of excitable tissues to hyperbaric environments has been shown to alter membrane ion conductances, but only little is known about the state of the membranes of intact cells in the post-decompression phase following a prolonged high-pressure treatment. Furthermore, almost nothing is known about high-pressure effects on skeletal muscle membranes. Therefore, we investigated changes to the input resistances, membrane potentials and voltage-gated membrane currents for sodium (INa), potassium (IK) and calcium (ICa) ions under voltage-clamp conditions in enzymatically isolated intact mammalian single fibers following a 3-hr high-pressure treatment up to 25 MPa at +4 degrees C. After a 3-hr 20 MPa treatment, the input resistance was increased but declined again for treatments with higher pressures. The resting membrane potentials were depolarized in the post-decompression phase following a 20-MPa high-pressure treatment; this could be explained by an increase in the Na+- over K+-permeability ratio and in intracellular [Na+]i. Following a 10-MPa high-pressure treatment, INa, IK and ICa amplitudes were similar compared to controls but were significantly reduced by 25 to 35% after a 3-hr 20-MPa high-pressure treatment. Interestingly, the voltage-dependent inactivation of INa and ICa seemed to be more stable at high pressures compared to the activation parameters, as no significant changes were found up to a 20-MPa treatment. For higher pressure applications (e.g., 25 MPa), there seemed to be a marked loss of membrane integrity and INa, IK and ICa almost disappeared.